THE CHARACTER AND MORAL VALUES IN “TO KILL A MOCKINGBIRD” BY HARPER LEE - Meity Dhaliani Sastrawijaya (Universitas Indraprasta PGRI, 2020)
The purpose of the research is to find out the character and the moral values in the novel “To Kill a Mockingbird” by Harper Lee. This research is designed as qualitative research. The approach that the writer uses is qualitative. The data are collected by analyzing the data found in the novel. The analysis of the novel is undertaken on the dialogues. The result of the research is the form of character and moral values. 1) The character that emerges in the novel “To Kill a Mockingbird” is the protagonist, antagonist, and foil characters. The protagonist is 70 %, the antagonist is 18 %, and the foil character is 12 %. It means that the character who dominates in the novel is the protagonist. This novel's point is to lead the readers to appreciate others 2) There are seven moral values in the novel: respect, kindness, conscience, self-control, empathy, tolerance, and fairness. The moral value in the novel, respect gets 28 %, kindness is 10 %, conscience is 15%, self-control is 5 %, empathy is 15%, tolerance is 13%, and fairness is 15%. It means that moral values that dominate in the novel convey particularly to the readers is respect.